Lithium ion battery, positive pole piece, positive active material, preparation method and electric device
By using the first lithium iron phosphate material and the second lithium iron phosphate material mixed with each other in the positive electrode sheet of the lithium ion battery, the problem that lithium ion battery is difficult to have both high energy density and high power performance is solved, and higher energy density and power performance are achieved.
Patent Information
- Application Number
- CN202510198888.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-04-08
AI Technical Summary
Existing lithium-ion batteries are difficult to have high energy density and high power performance.
The first lithium iron phosphate material and the second lithium iron phosphate material of a specific particle size that are mixed with each other are used as the positive electrode active material, and the compaction density of the electrode sheet is improved by controlling the difference in the average mass content of the doped elements and the difference in particle size.
The energy density and power performance of the battery are improved, and the compaction density of the positive electrode sheet is improved through the tightly packed lithium iron phosphate material particles.
Smart Images

Figure CN119786705A_ABST
Abstract
Description
[0001] Related Applications
[0002] This application is a divisional application of the Chinese patent application submitted by the applicant to the China Patent Office on October 25, 2024, with application number 2024114969809 and titled "Lithium-ion battery, positive electrode sheet, positive electrode active material, preparation method and electrical device". Technical Field
[0003] The present application relates to the technical field of lithium-ion batteries, and in particular to a lithium-ion battery, a positive electrode sheet, a positive electrode active material, a preparation method and an electrical device. Background Art
[0004] In recent years, as the application scope of lithium-ion batteries has become more and more extensive, lithium-ion batteries have been widely used in energy storage power systems such as hydropower, thermal power, wind power and solar power stations, as well as power tools, electric bicycles, electric motorcycles, electric vehicles, military equipment, aerospace and other fields. As lithium-ion batteries have made great progress, high energy density and high dynamics are one of the technical development directions of the industry, and higher requirements have been put forward for the energy density and power performance of lithium-ion batteries. Therefore, how to make lithium-ion batteries have both good energy density and power performance is an urgent problem to be solved. Summary of the invention
[0005] In order to achieve the above objectives, the present application provides a lithium-ion battery that has both good energy density and power performance.
[0006] In addition, the present application also provides a positive electrode sheet, a positive electrode active material, a preparation method and an electrical device.
[0007] In a first aspect of the present application, a lithium-ion battery is provided, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode film layer, wherein the positive electrode film layer comprises a positive electrode active material, wherein the positive electrode active material comprises a first lithium iron phosphate material and a second lithium iron phosphate material which are mixed with each other, wherein the first lithium iron phosphate material and the second lithium iron phosphate material contain doping elements, wherein the doping elements in the first lithium iron phosphate material and the second lithium iron phosphate material independently comprise one or more of titanium, vanadium, niobium and magnesium, wherein the difference between the average mass content of the doping elements in the first lithium iron phosphate material and the average mass content of the doping elements in the second lithium iron phosphate material is 1000ppm~8500ppm, and the average particle size of the primary particles of the first lithium iron phosphate material is greater than the average particle size of the primary particles of the second lithium iron phosphate material.
[0008] In the above-mentioned lithium-ion battery, the positive electrode plate contains a first lithium iron phosphate material and a second lithium iron phosphate material of a specific particle size and different particle sizes that are mixed and graded with each other, which can make the lithium iron phosphate material particles densely stacked, thereby achieving the effect of increasing the compaction density of the plate and thus increasing the energy density of the battery, wherein the average mass content of the doping elements of the large-particle-size first lithium iron phosphate material is higher, and the average mass content of the doping elements of the small-particle-size second lithium iron phosphate material is lower, and the difference in the average mass content of the two doping elements is controlled within a specific range. In this way, the large-particle-size lithium iron phosphate material has a higher doping content, which can make up for the defects of the large polarization and poor conductivity of the large-particle-size lithium iron phosphate material, improve its conductivity, and thereby improve the power performance of the battery.
[0009] In some embodiments, the lithium-ion battery meets one or more of the following characteristics:
[0010] (1) The average particle size of the primary particles of the first lithium iron phosphate material is 500 nm to 3100 nm;
[0011] (2) The average primary particle size of the second lithium iron phosphate material is 120 nm to 600 nm.
[0012] The average particle size of the primary particles of lithium iron phosphate is controlled within this range, so that the first lithium iron phosphate material can have good kinetic properties while also having its specific surface energy within a suitable range and controlling the side reactions with the electrolyte to a suitable degree, thereby enabling the lithium-ion battery to obtain better energy density and power performance.
[0013] The average particle size of the primary particles of the second lithium iron phosphate is controlled within this range, and can be graded with the first lithium iron phosphate material, and the lithium iron phosphate material particles are closely stacked, which can improve the compaction density of the pole piece to improve the energy density of the battery, so that the lithium-ion battery can obtain better energy density and power performance. In addition, controlling the lower limit of its average particle size is conducive to obtaining a slurry with suitable viscosity in the preparation process, which is convenient for process preparation.
[0014] In some embodiments, the lithium-ion battery meets one or more of the following characteristics:
[0015] (1) The average particle size of the primary particles of the first lithium iron phosphate material is 650nm~2600nm;
[0016] (2) The average primary particle size of the second lithium iron phosphate material is 150 nm to 580 nm.
[0017] In some embodiments, the difference between the average primary particle size of the first lithium iron phosphate material and the average primary particle size of the second lithium iron phosphate material is 200 nm to 2800 nm.
[0018] In some embodiments, the average mass content of the doping element in the first lithium iron phosphate material is 3000ppm~10000ppm.
[0019] In some embodiments, the average mass content of the doping element in the first lithium iron phosphate material is 4500ppm~9000ppm.
[0020] By controlling the average mass content of the doping elements in the first lithium iron phosphate material within the above range, the good stability of the first lithium iron phosphate material and the negative electrode SEI, the good gram capacity and kinetic performance of the first lithium iron phosphate material can be taken into account, thereby making the battery have both good energy density and power performance.
[0021] In some embodiments, the average mass content of the doping element in the second lithium iron phosphate material is 500ppm~5000ppm.
[0022] In some embodiments, the average mass content of the doping element in the second lithium iron phosphate material is 1000ppm~4000ppm.
[0023] By controlling the average mass content of the doping elements in the second lithium iron phosphate material within the above range, the good stability of the second lithium iron phosphate material and the negative electrode SEI, the good gram capacity and kinetic performance of the second lithium iron phosphate material can be taken into account, thereby enabling the battery to have both good energy density and power performance.
[0024] In some embodiments, the lithium-ion battery meets one or more of the following characteristics:
[0025] (1) The BET specific surface area of the first lithium iron phosphate material is 3 m 2 / g~9m 2 / g;
[0026] (2) The BET specific surface area of the second lithium iron phosphate material is 10 m 2 / g~25m 2 / g.
[0027] In some embodiments, the mass content of the first lithium iron phosphate material is 10% to 90% based on the total mass of the first lithium iron phosphate material and the second lithium iron phosphate material. By controlling the mass content of the first lithium iron phosphate material, the positive electrode sheet can obtain a higher compaction density, improve the energy density of the battery, and also take into account good power performance.
[0028] In some embodiments, based on the total mass of the first lithium iron phosphate material and the second lithium iron phosphate material, the mass content of the first lithium iron phosphate material is 30% to 70%.
[0029] In some embodiments, the first lithium iron phosphate material and the second lithium iron phosphate material both contain a carbon coating layer, and the mass content of carbon in the positive electrode active material is 0.8% to 2%. Controlling the mass content of carbon in the positive electrode active material can improve the conductivity of the positive electrode active material and improve the power performance of the battery.
[0030] In some embodiments, the positive electrode active material accounts for 80% to 98% by mass in the positive electrode film layer.
[0031] In some embodiments, one or more of the following conditions are met:
[0032] (1) The compaction density of the positive electrode film layer on one side of the positive electrode sheet is 2.3 g / cc to 2.8 g / cc;
[0033] (2) The DC internal resistance of the lithium-ion battery at 25° C. and 10% SOC is 800 mΩ to 1300 mΩ.
[0034] In some embodiments, the lithium-ion battery further comprises a negative electrode plate, the negative electrode plate comprises a negative electrode film layer, the negative electrode film layer comprises a negative electrode active material, and the negative electrode active material comprises one or more of graphite, soft carbon, hard carbon, silicon-based material, tin-based material and lithium titanate.
[0035] In some embodiments, the negative electrode active material includes graphite.
[0036] In some embodiments, the negative electrode active material includes graphite and silicon-based material, and in the negative electrode active material, the mass content of the silicon-based material is 0.5% to 20%.
[0037] In some embodiments, the lithium-ion battery further includes an electrolyte, and the conductivity of the electrolyte is 12 mS / cm~20 mS / cm.
[0038] In a second aspect of the present application, a positive electrode plate is provided, the positive electrode plate comprising a positive electrode film layer, the positive electrode film layer comprising a positive electrode active material, the positive electrode active material comprising a first lithium iron phosphate material and a second lithium iron phosphate material mixed with each other, the first lithium iron phosphate material and the second lithium iron phosphate material containing doping elements, the doping elements in the first lithium iron phosphate material and the second lithium iron phosphate material each independently comprising one or more of titanium, vanadium, niobium and magnesium, the difference between the average mass content of the doping elements in the first lithium iron phosphate material and the average mass content of the doping elements in the second lithium iron phosphate material is 1000ppm~8500ppm, and the average particle size of the primary particles of the first lithium iron phosphate material is larger than the average particle size of the primary particles of the second lithium iron phosphate material.
[0039] In a third aspect of the present application, a positive electrode active material is provided, the positive electrode active material comprising a first lithium iron phosphate material and a second lithium iron phosphate material, the first lithium iron phosphate material and the second lithium iron phosphate material containing doping elements, the doping elements in the first lithium iron phosphate material and the second lithium iron phosphate material each independently comprising one or more of titanium, vanadium, niobium and magnesium, the difference between the average mass content of the doping elements in the first lithium iron phosphate material and the average mass content of the doping elements in the second lithium iron phosphate material is 1000ppm~8500ppm, and the average particle size of the primary particles of the first lithium iron phosphate material is greater than the average particle size of the primary particles of the second lithium iron phosphate material.
[0040] In a fourth aspect of the present application, a method for preparing a positive electrode active material is provided, comprising the following steps:
[0041] Prepare a first lithium iron phosphate material and a second lithium iron phosphate material, wherein the first lithium iron phosphate material and the second lithium iron phosphate material contain doping elements, and the doping elements in the first lithium iron phosphate material and the second lithium iron phosphate material independently include one or more of titanium, vanadium, niobium and magnesium;
[0042] Mixing the first lithium iron phosphate material and the second lithium iron phosphate material to obtain the positive electrode active material;
[0043] Among them, the difference between the average mass content of the doping element in the first lithium iron phosphate material and the average mass content of the doping element in the second lithium iron phosphate material is 1000ppm~8500ppm, and the average particle size of the primary particles of the first lithium iron phosphate material is larger than the average particle size of the primary particles of the second lithium iron phosphate material.
[0044] In some embodiments, at least one of the following conditions is met:
[0045] (1) Preparing the first lithium iron phosphate material comprises the following steps: mixing a first lithium source, a first phosphorus source, a first iron source and a first doping source with a first solvent to obtain a first slurry, drying to remove the first solvent, and performing a first sintering treatment; performing a second sintering treatment on the powder obtained by the first sintering treatment, wherein the insulation temperature of the second sintering treatment is higher than the insulation temperature of the first sintering treatment, to obtain the first lithium iron phosphate material; the first doping source comprises one or more of titanium, vanadium, niobium and magnesium;
[0046] (2) The preparation of the second lithium iron phosphate material comprises the following steps: mixing a second lithium source, a second phosphorus source, a second iron source and a second doping source with a second solvent to obtain a second slurry, drying to remove the second solvent, and performing a third sintering treatment to obtain a second lithium iron phosphate material; the second doping source comprises one or more of titanium, vanadium, niobium and magnesium.
[0047] In some embodiments, the first doping source and the second doping source independently include one or more of titanium dioxide, vanadium pentoxide, n-butyl titanate, niobium pentoxide, niobium oxalate, niobium ethoxide, magnesium hydroxide, magnesium nitrate and ammonium metavanadate.
[0048] In some embodiments, the preparation method satisfies one or more of the following conditions:
[0049] (1) The first sintering treatment has a holding temperature of 500°C to 760°C and a holding time of 1h to 6h;
[0050] (2) The holding temperature of the second sintering treatment is 720°C to 780°C, and the holding time is 2h to 12h;
[0051] (3) The insulation temperature of the third sintering treatment is 600°C to 800°C, and the insulation time is 2h to 24h.
[0052] In some embodiments, the preparation method satisfies one or more of the following conditions:
[0053] (1) further comprising the step of controlling the Dv50 particle size of the first slurry to be between 350 nm and 1200 nm;
[0054] (2) The method further includes controlling the Dv50 particle size of the second slurry to be between 50 nm and 400 nm.
[0055] In some embodiments, the first lithium iron phosphate material and the second lithium iron phosphate material both contain a carbon coating layer, and the mass content of carbon in the first lithium iron phosphate material or in the second lithium iron phosphate material is independently 0.8% to 2%;
[0056] The mass content of carbon element in the powder obtained by the first sintering process is 0.01%~0.79%.
[0057] In the fifth aspect of the present application, an electrical device is provided, comprising the lithium-ion battery provided in the first aspect of the present application, the positive electrode plate provided in the second aspect of the present application, the positive electrode active material provided in the third aspect of the present application, and at least one of the positive electrode active materials prepared by the preparation method provided in the fourth aspect of the present application.
[0058] The electric device of the present application includes the lithium-ion battery provided by the present application, and thus has at least the same advantages as the lithium-ion battery.
[0059] The details of one or more embodiments of the present application are set forth in the following drawings and description. Other features, objects, and advantages of the present application will become apparent from the description, drawings, and claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] In order to better describe and illustrate the embodiments or examples provided by the present application, reference may be made to one or more drawings. The additional details or examples used to describe the drawings should not be considered as limiting the scope of the disclosed application, the embodiments or examples currently described, and any of the best modes of these applications currently understood. Moreover, the same reference numerals are used throughout the drawings to represent the same components. In the drawings:
[0061] Figure 1 FIG. 1 is a schematic diagram of a lithium-ion battery according to an embodiment of the present application.
[0062] Figure 2 yes Figure 1 An exploded view of a lithium-ion battery according to an embodiment of the present application is shown.
[0063] Figure 3 is a schematic diagram of a battery module according to an embodiment of the present application.
[0064] Figure 4 It is a schematic diagram of a battery pack according to one embodiment of the present application.
[0065] Figure 5 yes Figure 4 An exploded view of a battery pack according to an embodiment of the present application is shown.
[0066] Figure 6 Schematic diagram of an electrical device using a lithium-ion battery as a power source according to an embodiment of the present application.
[0067] Description of reference numerals:
[0068] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module; 5. Battery cell; 51. Shell; 52. Electrode assembly; 53. Cover plate; 6. Electrical device. DETAILED DESCRIPTION
[0069] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0070] "Scope" disclosed in the present application can be limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or excluding end values, and any end value can be included or not included independently, and can be combined arbitrarily, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 listed, and if the maximum range values 3,4 and 5 are also listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc. For example, when a parameter is expressed as an integer selected from "2-10", it is equivalent to listing the integers 2, 3, 4, 5, 6, 7, 8, 9 and 10.
[0071] In the present application, "plurality", "multiple" and the like, unless otherwise specified, refer to a number greater than or equal to 2. For example, "one or more" means one or greater than or equal to two.
[0072] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0073] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment or implementation of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments. The "implementation methods" mentioned herein have a similar understanding.
[0074] Those skilled in the art will appreciate that, in the methods of each embodiment or example, the order in which each step is written does not mean a strict order of execution and does not constitute any limitation on the implementation process, and the detailed order of execution of each step should be determined by its function and possible internal logic. If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), indicating that the method may include steps (a) and (b) performed sequentially, or steps (b) and (a) performed sequentially. For example, the method may also include step (c), indicating that step (c) can be added to the method in any order, for example, the method may include steps (a), (b) and (c), or steps (a), (c) and (b), or steps (c), (a) and (b), etc.
[0075] In this application, unless otherwise specified, A (such as B) means that B is a non-limiting example of A, and it can be understood that A is not limited to B.
[0076] In this application, "optionally", "optional", and "optional" mean optional, that is, any one of the two parallel schemes of "yes" or "no". If there are multiple "options" in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "option" is independent.
[0077] As described in the background art, how to make lithium-ion batteries have both good energy density and power performance is an urgent problem to be solved.
[0078] The realization of high energy density of batteries requires high energy density electrode plates. For example, for the positive electrode plate of the battery, to achieve high energy density of the positive electrode plate, the positive electrode plate needs to have a higher positive electrode plate compaction density. One direction to improve the compaction density of the positive electrode plate is to achieve dense stacking of the positive electrode active materials.
[0079] The premise for the cathode active material to form a dense stack is that the material has different particle sizes. For example, lithium iron phosphate materials with nanometer particle sizes and lithium iron phosphate materials with micrometer particle sizes are mixed to increase the compaction density of the cathode pole piece and achieve high energy density of the battery. However, in actual production, it is found that traditional lithium iron phosphate materials with high compaction density are difficult to make the battery have good energy density and power performance.
[0080] Nanoscale lithium iron phosphate materials have excellent electronic and ionic conductivity, but when the particle size of lithium iron phosphate particles is increased to, for example, micrometer level, the electronic and ionic conductivity decreases. Therefore, large-size particles in lithium iron phosphate materials with higher compaction density will seriously affect the power performance of the battery cell. The ionic conductivity of lithium iron phosphate materials can be improved by doping lithium iron phosphate with dopants containing metal elements; or by increasing the amount of carbon source added and the amount of carbon coating layer coated, the conductivity of the surface of lithium iron phosphate materials can be improved. In this way, the kinetic properties of lithium iron phosphate materials can be improved to a certain extent by doping lithium iron phosphate with metal elements or coating lithium iron phosphate with carbon, thereby improving its power performance. Therefore, attempts were made to de-dope metal elements in the process of preparing lithium iron phosphate materials with higher compaction density by one-step sintering. However, since the dopants added in the one-step sintering process are unevenly distributed on the surface of particles of different particle sizes, specifically, the surface energy of small-size particles is higher, so it is easier to react with dopants, and the doping content of metal elements is higher; while the surface energy of large-size particles is lower, so compared with small-size particles, the doping content of metal elements in large-size particles is lower. Similarly, compared to small-sized particles, large-sized particles also have a lower carbon coating content. In addition, the presence of carbon will affect the growth of lithium iron phosphate particles, and it is also difficult to obtain large-sized particles with a high carbon coating content. Therefore, these methods are not effective in improving the kinetic properties of lithium iron phosphate materials with higher compaction density, and it is still difficult for the battery to have both good energy density and power performance. Based on this, the present application provides a method for preparing a positive electrode active material with improved process, and the prepared positive electrode active material contains lithium iron phosphate materials of different particle sizes, and can make large-sized lithium iron phosphate particles have a higher doping content, thereby improving the kinetic properties of the positive electrode active material on the basis of taking into account a good compaction density, and then improving its power performance. In addition, a positive electrode sheet and a lithium-ion battery using this positive electrode active material are also provided, which can have both good energy density and power performance.
[0081] In a first aspect, the present application provides a lithium-ion battery, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode film layer, wherein the positive electrode film layer comprises a positive electrode active material, wherein the positive electrode active material comprises a first lithium iron phosphate material and a second lithium iron phosphate material that are mixed with each other, wherein the first lithium iron phosphate material and the second lithium iron phosphate material contain doping elements, wherein the doping elements in the first lithium iron phosphate material and the second lithium iron phosphate material independently comprise one or more of titanium, vanadium, niobium and magnesium, wherein the difference between the average mass content of the doping elements in the first lithium iron phosphate material and the average mass content of the doping elements in the second lithium iron phosphate material is 1000ppm~8500ppm, and the average particle size of the primary particles of the first lithium iron phosphate material is greater than the average particle size of the primary particles of the second lithium iron phosphate material.
[0082] In the above-mentioned lithium-ion battery, the positive electrode plate contains a first lithium iron phosphate material and a second lithium iron phosphate material of a specific particle size and different particle sizes that are mixed and graded with each other, which can make the lithium iron phosphate material particles densely stacked, thereby achieving the effect of increasing the compaction density of the plate and thus increasing the energy density of the battery, wherein the average mass content of the doping elements of the large-particle-size first lithium iron phosphate material is higher, and the average mass content of the doping elements of the small-particle-size second lithium iron phosphate material is lower, and the difference in the average mass content of the two doping elements is controlled within a specific range. In this way, the large-particle-size lithium iron phosphate material has a higher doping content, which can make up for the defects of the large polarization and poor conductivity of the large-particle-size lithium iron phosphate material, improve its conductivity, and thereby improve the power performance of the battery.
[0083] The following method can be used to detect the average particle size of the primary particles of the first lithium iron phosphate material and the second lithium iron phosphate material in the positive electrode sheet of the battery and the average mass content of the doping elements:
[0084] Disassemble the battery to obtain the positive electrode plate, peel off the positive electrode film layer of the positive electrode plate, use acetone to fully wash the positive electrode film layer, filter and dry to obtain a powder. Take 0.05g of the evenly mixed powder and dissolve it in 40mL of anhydrous ethanol, then add an appropriate amount of dispersant, stir evenly to obtain a suspension, take 2mL of the suspension and 2mL of anhydrous ethanol and mix them for ultrasonic treatment. The ultrasonic power is 480W, and the ultrasonic time is 5min. The uniformly dispersed suspension obtained, take an appropriate amount of the middle layer suspension for transmission electron microscopy test to obtain a transmission electron microscope image. It can be understood that the lithium iron phosphate material of the positive electrode plate in this application can be one or more of primary particles and secondary particles. After being dispersed by ultrasonic treatment in this test method, it mainly exists as primary particles.
[0085] 5-10 transmission electron microscope images with 50 to 100 particles are selected as the sampling area to ensure that at least 500 particles are tested. Then, the projection area of each primary particle in each sampling area can be counted through the Avizo 3D software image processing software, which is the primary particle cross-sectional area S. Among them, when identifying primary particles, for particles with obvious adhesion, manual identification and software identification can be combined to determine whether the particles belong to a single primary particle or a secondary particle. The equivalent circle method is used to obtain the equivalent circle diameter of the primary particle, which is the primary particle size d of the primary particle; at the same time, the transmission electron microscope accessory EDS energy spectrum is used to perform elemental analysis on each primary particle. The test point is the middle part of the transmission surface of each particle, and the mass content of the doping element of each primary particle in the sampling area is obtained.
[0086] The mass content of the doping element and the corresponding primary particle size of each primary particle in multiple sampling areas are counted, for example, the primary particle size is used as the horizontal coordinate, and the mass content of the doping element is used as the vertical coordinate, and the position of each primary particle in the coordinate is shown. Through the distribution of the primary particles in the coordinate, it is obvious that there are two areas where the mass content of the doping element is relatively concentrated. For particles that deviate from the above two areas individually or in small amounts during the statistical process, such as primary particles with a small particle size but a high doping amount and primary particles with a large particle size but a small doping amount, they are divided into the first lithium iron phosphate particles and the second lithium iron phosphate particles based on the doping amount, which are located on the upper and lower sides parallel to the horizontal coordinate, respectively, wherein the area with a higher mass content of the doping element is the first lithium iron phosphate material, and the area with a lower mass content of the doping element is the second lithium iron phosphate material. It is worth noting that in the same positive electrode plate, there is a large difference in the doping amount of the first lithium iron phosphate material and the second lithium iron phosphate material. In the present application, the difference between the mass content of the doping element in the first lithium iron phosphate material and the mass content of the doping element in the second lithium iron phosphate material is controlled to be 1000ppm~8500ppm. Therefore, in the reverse detection of the first lithium iron phosphate material and the second lithium iron phosphate material in the positive electrode plate, it can be obviously obtained that the area with a higher mass content of the doping element is the first lithium iron phosphate material, and the area with a lower mass content of the doping element is the second lithium iron phosphate material.
[0087] The sum of the primary particle sizes of all first lithium iron phosphate materials is counted and divided by the total number of all first lithium iron phosphate materials to obtain the average primary particle size of the first lithium iron phosphate materials. The sum of the mass contents of the doping elements in all first lithium iron phosphate materials is counted and divided by the total number of all first lithium iron phosphate materials to obtain the average mass content of the doping elements in the first lithium iron phosphate materials.
[0088] The sum of the primary particle sizes of all second lithium iron phosphate materials is counted and divided by the total number of all second lithium iron phosphate materials to obtain the average primary particle size of the second lithium iron phosphate materials. The sum of the mass contents of the doping elements in all second lithium iron phosphate materials is counted and divided by the total number of all second lithium iron phosphate materials to obtain the average mass content of the doping elements in the second lithium iron phosphate materials.
[0089] In the statistical process of the primary particles, the primary particles with a primary particle size of less than 50 nm are not included in the statistical range. That is, the primary particles with a primary particle size greater than or equal to 50 nm are effective particles. This is because the number of primary particles with a primary particle size of less than 50 nm is very small in the system of the present application, and if they are included in the test, it will bring a large error to the test result.
[0090] In some of these embodiments, the first lithium iron phosphate particles include primary particles.
[0091] In some of these embodiments, the second lithium iron phosphate particles include primary particles.
[0092] For the average particle size of the primary particles of lithium iron phosphate materials, controlling the average particle size of the primary particles to be above the lower limit particle size can reduce the degree of side reactions between the lithium iron phosphate material and the electrolyte, reduce the specific surface energy of the lithium iron phosphate material to make it within a suitable range, and is conducive to the battery's charge and discharge capacity; controlling the upper limit particle size of the average particle size of the primary particles can make the lithium iron phosphate material have good dynamic performance within this range. At the same time, a larger average particle size of the primary particles of the lithium iron phosphate material will reduce its dynamic performance, thereby affecting the battery's charge and discharge capacity. In addition, through the particle size grading of the lithium iron phosphate material to achieve good tight stacking, the positive electrode plate can have a higher compaction density. Therefore, the average particle size of the primary particles of the first lithium iron phosphate material and the second lithium iron phosphate material is controlled within the following range, so that the lithium-ion battery obtains good energy density and power performance.
[0093] In some embodiments, the average primary particle size of the first lithium iron phosphate material is 500nm to 3100nm. The average primary particle size of the first lithium iron phosphate is controlled within this range, so that the first lithium iron phosphate material can have good kinetic properties, and its specific surface energy can be within a suitable range, and the side reaction with the electrolyte can be controlled to a suitable degree, so that the lithium-ion battery can obtain good energy density and power performance.
[0094] As an example, the average particle size of the primary particles of the first lithium iron phosphate material may be 500nm, 550nm, 600nm, 650nm, 700nm, 800nm, 1000nm, 1200nm, 1500nm, 1800nm, 2000nm, 2200nm, 2500nm, 2600nm, 2800nm, 3000nm, 3100nm, or within the range formed by any two of the above point values as end values. In some embodiments, the average particle size of the primary particles of the first lithium iron phosphate material is 650nm~2600nm, so that the lithium-ion battery has better energy density and power performance.
[0095] In some embodiments, the average particle size of the primary particles of the second lithium iron phosphate material is 120nm~600nm. The average particle size of the primary particles of the second lithium iron phosphate is controlled within this range, and can be graded with the first lithium iron phosphate material. The lithium iron phosphate material particles are closely stacked, which can improve the compaction density of the pole piece to improve the energy density of the battery, so that the lithium-ion battery can obtain good energy density and power performance. In addition, controlling the lower limit of its average particle size is conducive to obtaining a slurry with suitable viscosity in the preparation process, which is convenient for process preparation.
[0096] As an example, the average primary particle size of the second lithium iron phosphate material can be 120nm, 150nm, 180nm, 200nm, 250nm, 280nm, 300nm, 350nm, 400nm, 450nm, 480nm, 500nm, 580nm, 600nm, or a range consisting of any two of the above point values as end values. In some embodiments, the average primary particle size of the second lithium iron phosphate material is 150nm~480nm, so that the lithium-ion battery has better energy density and power performance.
[0097] In some embodiments, the difference between the average particle size of the primary particles of the first lithium iron phosphate material and the average particle size of the primary particles of the second lithium iron phosphate material is 200nm~2800nm. As an example, the difference between the average particle size of the primary particles of the first lithium iron phosphate material and the average particle size of the primary particles of the second lithium iron phosphate material can be 200nm, 300nm, 400nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 780nm, 800nm, 1000nm, 1200nm, 1500nm, 1800nm, 2000nm, 2200nm, 2500nm, 2700nm, 2800nm, or within the range formed by any two of the above point values as end values. Further, the difference between the average particle size of the primary particles of the first lithium iron phosphate material and the average particle size of the primary particles of the second lithium iron phosphate material is 600nm~2700nm. By further controlling the difference in the average particle sizes of the primary particles of the two, the first lithium iron phosphate material and the second lithium iron phosphate material can be stacked more closely when graded, thereby achieving a better compaction density of the positive electrode sheet.
[0098] For lithium iron phosphate materials, controlling the upper limit content of its doping elements can make the doping elements basically enter the lattice, reduce its enrichment on the surface of lithium iron phosphate materials, reduce the risk of dissolution in the negative electrode to destroy the negative electrode SEI film, and improve the stability of lithium iron phosphate materials and negative electrode SEI; in addition, too many doping elements will affect the gram capacity of lithium iron phosphate materials, so controlling the upper limit content of doping elements can make the gram capacity of lithium iron phosphate materials basically unaffected, thereby enabling the battery to obtain good energy density. For lithium iron phosphate materials, controlling its doping elements above the lower limit content can improve the kinetic properties of lithium iron phosphate materials and thus improve the power performance of the battery. Therefore, controlling the doping content of the first lithium iron phosphate material and the second lithium iron phosphate material within the following range can enable the battery to have both good energy density and power performance. Further, on this basis, combined with the control of the average particle size of the primary particles of the first lithium iron phosphate material and the second lithium iron phosphate material, the compaction density of the positive electrode sheet can be improved, so that the battery can have both better energy density and power performance.
[0099] Therefore, in some embodiments, the average mass content of the doping element in the first lithium iron phosphate material is 3000ppm~10000ppm. As an example, based on the mass of the first lithium iron phosphate material, the average mass content of the doping element in the first lithium iron phosphate material can be 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, 6000ppm, 6500ppm, 7000ppm, 7500ppm, 8000ppm, 8500ppm, 9000ppm, 9500ppm, 10000ppm, or within the range formed by any two of the above point values as end values. Further, based on the mass of the first lithium iron phosphate material, the average mass content of the doping element in the first lithium iron phosphate material is 4500ppm~9000ppm. By controlling the average mass content of the doping elements in the first lithium iron phosphate material within the above range, the good stability of the first lithium iron phosphate material and the negative electrode SEI, the good gram capacity and kinetic performance of the first lithium iron phosphate material can be taken into account, thereby making the battery have both good energy density and power performance.
[0100] In some embodiments, the average mass content of the doping element in the second lithium iron phosphate material is 500ppm~5000ppm. As an example, the average mass content of the doping element in the second lithium iron phosphate material can be 500ppm, 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, or within the range formed by any two of the above point values as end values. Further, based on the mass of the second lithium iron phosphate material, the average mass content of the doping element in the second lithium iron phosphate material is 1000ppm~4000ppm. In this way, the average mass content of the doping element in the second lithium iron phosphate material is controlled within the above range, which can take into account the good stability of the second lithium iron phosphate material and the negative electrode SEI, the good gram capacity and kinetic performance of the second lithium iron phosphate material, and thus make the battery have good energy density and power performance.
[0101] As an example, the difference between the average mass content of the doping element in the first lithium iron phosphate material and the average mass content of the doping element in the second lithium iron phosphate material can be 1000ppm, 1500ppm, 2000ppm, 2500ppm, 3000ppm, 3500ppm, 4000ppm, 4500ppm, 5000ppm, 5500ppm, 6000ppm, 6500ppm, 7000ppm, 7500ppm, 8000ppm, 8500ppm, or within the range formed by any two of the above point values as end values. Further, the difference between the average mass content of the doping element in the first lithium iron phosphate material and the average mass content of the doping element in the second lithium iron phosphate material is 1500ppm~8000ppm, or 2500ppm~5500ppm, or 3000ppm~5000ppm, or 4000ppm~5000ppm.
[0102] The specific types of doping elements of the first lithium iron phosphate material and the second lithium iron phosphate material may be the same or different.
[0103] In some embodiments, the BET specific surface area of the first lithium iron phosphate material is 3 m 2 / g~9m 2 / g; As an example, the BET specific surface area of the first lithium iron phosphate material can be 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, or within the range consisting of any two of the above point values as end values.
[0104] In some embodiments, the BET specific surface area of the second lithium iron phosphate material is 10 m 2 / g~25m 2 As an example, the BET specific surface area of the second lithium iron phosphate material is 10 m 2 / g, 12m 2 / g, 15m 2 / g, 16m 2 / g, 18m 2 / g, 20m 2 / g, 22m 2 / g, 25m 2 / g, or within the range consisting of any two of the above point values as end values.
[0105] In this article, the BET specific surface area can refer to GB / T19587-2017, and is tested by the nitrogen adsorption specific surface area analysis test method and calculated by the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis test can be performed by the Tri-Star3020 specific surface area pore size analysis tester of Micromeritics, USA.
[0106] In some embodiments, the mass content of the first lithium iron phosphate material is 10% to 90% based on the total mass of the first lithium iron phosphate material and the second lithium iron phosphate material. By controlling the mass content of the first lithium iron phosphate material within the above range, the positive electrode sheet can obtain a good compaction density, so that the battery has a good energy density, and at the same time, good power performance can be taken into account. As an example, the mass content of the first lithium iron phosphate material is 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, or within the range formed by any two of the above point values as end values. Further, based on the total mass of the first lithium iron phosphate material and the second lithium iron phosphate material, the mass content of the first lithium iron phosphate material is 25%-85% or 30% to 70%. Further, by controlling the mass content of the first lithium iron phosphate material within the above range, the positive electrode sheet can obtain a higher compaction density, improve the energy density of the battery, and at the same time, good power performance can be taken into account.
[0107] Based on the total mass of the first lithium iron phosphate material and the second lithium iron phosphate material, the mass content of the first lithium iron phosphate material can be indirectly tested by obtaining the area ratio of the first lithium iron phosphate material to the total area of the first lithium iron phosphate material and the second lithium iron phosphate material through detection of the average particle size of the primary particles of the first lithium iron phosphate material and the second lithium iron phosphate material in the positive electrode plate of the above battery.
[0108] Specifically, the equivalent circle area is calculated using the equivalent circle method according to the projected area of each primary particle counted in each sampling area. The area ratio of the first lithium iron phosphate material to the total area of the first lithium iron phosphate material and the second lithium iron phosphate material can be obtained by dividing all the equivalent circle areas corresponding to the first lithium iron phosphate particles by the equivalent circle areas of the total particles of the first lithium iron phosphate material and the second lithium iron phosphate material.
[0109] In some embodiments, based on the total mass of the first lithium iron phosphate material and the second lithium iron phosphate material, the mass content of the first lithium iron phosphate material is 10%~90%, and can be optionally 25%-85%; correspondingly, the area content of the first lithium iron phosphate material in the total area of the first lithium iron phosphate material and the second lithium iron phosphate material is 5%~85%; preferably 20%~80%.
[0110] In some embodiments, the first lithium iron phosphate material and the second lithium iron phosphate material both contain a carbon coating layer, and the mass content of carbon in the positive electrode active material is 0.8% to 2%. As an example, the mass content of carbon in the positive electrode active material can be 0.8%, 1%, 1.2%, 1.5%, 1.6%, 1.8%, 2%, or within the range formed by any two of the above point values as end values. Controlling the mass content of carbon in the positive electrode active material can improve the conductivity of the positive electrode active material and improve the power performance of the battery.
[0111] In some of the embodiments, the positive electrode active material is 80% to 98% by mass in the positive electrode film layer; as an example, it can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, or within the range consisting of any two of the above point values as end values.
[0112] In some embodiments, the compaction density of the positive electrode film layer on one side of the positive electrode sheet is 2.3 g / cc (grams per cubic centimeter) to 2.8 g / cc. As an example, the compaction density can be 2.3 g / cc, 2.4 g / cc, 2.5 g / cc, 2.6 g / cc, 2.7 g / cc, 2.8 g / cc, or within a range consisting of any two of the above point values as end values.
[0113] In some of the embodiments, the DC internal resistance of the lithium-ion battery at 25° C. and 10% SOC is 800 mΩ to 1300 mΩ, further 800 mΩ to 1200 mΩ, further 800 mΩ to 1100 mΩ, 800 mΩ to 1000 mΩ, or 800 mΩ to 900 mΩ.
[0114] The second aspect of the present application provides a positive electrode plate, as described above, which will not be repeated here.
[0115] In a third aspect of the present application, a positive electrode active material is provided, comprising the first lithium iron phosphate material and the second lithium iron phosphate material.
[0116] A fourth aspect of the present application provides a method for preparing a positive electrode active material, comprising the following steps S10 to S20.
[0117] S10. Prepare a first lithium iron phosphate material and a second lithium iron phosphate material, wherein the first lithium iron phosphate material and the second lithium iron phosphate material contain doping elements, and the doping elements in the first lithium iron phosphate material and the second lithium iron phosphate material independently include one or more of titanium, vanadium, niobium and magnesium.
[0118] S20, mixing the first lithium iron phosphate material and the second lithium iron phosphate material to obtain the positive electrode active material.
[0119] Among them, the difference between the average mass content of the doping element in the first lithium iron phosphate material and the average mass content of the doping element in the second lithium iron phosphate material is 1000ppm~8500ppm, and the average particle size of the primary particles of the first lithium iron phosphate material is larger than the average particle size of the primary particles of the second lithium iron phosphate material. In the preparation method of the above-mentioned positive electrode active material, the first lithium iron phosphate material with large particles is doped with the above-mentioned doping elements alone, so that the average mass content of the doping elements in the first lithium iron phosphate material can be larger. Specifically, the difference between the average mass content of the doping elements in the first lithium iron phosphate material and the average mass content of the doping elements in the second lithium iron phosphate material is 1000ppm~8500ppm. In this way, the large-particle lithium iron phosphate material has a higher doping content, which can make up for the defects of large polarization and poor conductivity of the large-particle lithium iron phosphate material, improve its conductivity, and then improve the kinetic properties of the large-particle first lithium iron phosphate material; then the first lithium iron phosphate material and the second lithium iron phosphate material are mixed, so that the lithium iron phosphate material particles can be closely stacked, so as to achieve the effect of increasing the compaction density of the pole piece to increase the energy density of the battery; in this way, the lithium-ion battery can have both good energy density and power performance.
[0120] The traditional one-step method of sintering doped lithium iron phosphate of different particle sizes to obtain large-size particles has a doping content of metal elements that is difficult to reach 3000ppm (far below 3000ppm), and the doping content of metal elements in large-size particles is lower than that in small-size particles. The average mass content of the doping elements in the first lithium iron phosphate material prepared by the above preparation method is 3000ppm~10000ppm, and further 4500ppm~9000ppm.
[0121] It can be understood that the above preparation method can produce the positive electrode active material mentioned above in the present application.
[0122] In some embodiments, S10 includes the following steps: mixing a first lithium source, a first phosphorus source, a first iron source, and a first doping source with a first solvent to obtain a first slurry, drying to remove the first solvent, and performing a first sintering treatment; performing a second sintering treatment on the powder obtained by the first sintering treatment, wherein the insulation temperature of the second sintering treatment is higher than the insulation temperature of the first sintering treatment, to obtain a first lithium iron phosphate material. The first lithium iron phosphate material with a larger particle size can be obtained by the secondary sintering treatment with an increased temperature gradient.
[0123] In step S10 of preparing the first lithium iron phosphate material, the average particle size of the primary particles of the first lithium iron phosphate material can be adjusted to 500nm~3000nm by controlling the first sintering temperature and the second sintering temperature. Further, the particle size of the first slurry obtained in step S10 can also be adjusted to adjust the average particle size of the primary particles of the first lithium iron phosphate material. It is understandable that the average particle size of the primary particles of the first lithium iron phosphate material can be adjusted by adjusting one or both of the sintering temperature and the slurry particle size.
[0124] In some embodiments, the Dv50 particle size of the first slurry obtained in S10 is further controlled to be 350 nm to 1200 nm; as an example, it may be 350 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1000 nm, 1100 nm, 1200 nm, or within the range formed by any two of the above point values.
[0125] Dv50 is a well-known meaning in the art and can be measured by methods known in the art, for example, using a laser particle size analyzer (such as Malvern Master Size 3000). Dv50 represents the particle size corresponding to the cumulative volume distribution percentage of particles from the smallest particle size to 50% according to the particle size volume distribution.
[0126] The particle size volume distribution can be obtained by the following method: take a clean beaker, add an appropriate amount of the sample to be tested, and fully ultrasonicate to ensure that the sample is completely dispersed. The test instrument is Malvern 2000 of the United States. After the sample is poured into the injection tower, it circulates with the solution to the test optical path system. When the particles are irradiated by the laser beam, the particle size distribution characteristics of the particles can be obtained by receiving and measuring the energy distribution of the scattered light (shading degree: 8-12%). Draw a particle size volume distribution diagram based on the test data.
[0127] Further, the first doping source includes one or more of titanium, vanadium, niobium and magnesium. As an example, the first doping source includes one or more of titanium dioxide, vanadium pentoxide, n-butyl titanate, niobium pentoxide, niobium oxalate, niobium ethoxide, magnesium hydroxide, magnesium nitrate and ammonium metavanadate.
[0128] Further, the holding temperature of the first sintering treatment is 500°C~760°C, and the holding time is 1h~6h, which can be 2h~6h. As an example, the holding temperature of the first sintering treatment can be 500°C, 550°C, 600°C, 650°C, 700°C, 720°C, 750°C, 760°C, or within the range formed by any two of the above point values as end values. As an example, the holding time can be 1h, 2h, 3h, 4h, 5h, 26h, or within the range formed by any two of the above point values as end values.
[0129] Further, the holding temperature of the second sintering treatment is 720°C~780°C, and the holding time is 2h~12h, and can be 2h~6h; as an example, the holding temperature of the second sintering treatment can be 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, or in the range formed by any two of the above point values as end values. As an example, the holding time can be 2h, 3h, 4h, 5h, 26h, or in the range formed by any two of the above point values as end values.
[0130] Furthermore, the first lithium iron phosphate material also contains a carbon coating layer, and the mass content of carbon in the first lithium iron phosphate material is 0.8% to 2%. In step S10, a carbon source for forming a carbon coating layer is added to the first slurry accordingly. A carbon source for forming a coating layer is also added in the second sintering process.
[0131] Furthermore, the step of adding a carbon source for forming a coating layer in the second sintering process includes the following steps: adding a solvent and a carbon source to the powder obtained in the first sintering process to form a slurry; and then performing a second sintering process on the slurry, so that the first lithium iron phosphate material forms a carbon coating layer. Furthermore, before performing the second sintering process on the slurry, the step of drying the slurry to remove the solvent is also included.
[0132] In this way, the mass content of carbon in the powder obtained by the first sintering treatment is less than the mass content of carbon in the first lithium iron phosphate material. This is because the presence of carbon will affect the growth of lithium iron phosphate particles. Therefore, if more carbon sources are added to the first slurry, the growth of lithium iron phosphate particles will be inhibited, making it difficult to obtain a first lithium iron phosphate material with a large particle size; in this way, by adding a carbon source in two steps and controlling the amount of carbon source added in the first step to be less, the lithium iron phosphate particles can be promoted to grow, and then combined with the secondary sintering to add a carbon source, the desired large particle size and the desired carbon coating amount are obtained, so that the conductivity of the first lithium iron phosphate material is improved by carbon coating, the kinetic performance of the first lithium iron phosphate material is improved, and then the power performance of the battery is improved. This method can be applied to the preparation of large-particle carbon-coated lithium iron phosphate materials with doped or undoped large particles, so as to obtain lithium iron phosphate materials with larger particle sizes and larger carbon coating amounts, such as carbon-coated lithium iron phosphate materials with an average primary particle size of 500nm~3100nm.
[0133] Furthermore, the mass content of carbon in the powder obtained by the first sintering process is 0.01% to 0.79%. The amount of carbon source added to the first slurry is such that the mass content of carbon in the powder obtained by the first sintering process is 0.01% to 0.79%.
[0134] Furthermore, the mass content of carbon in the first lithium iron phosphate material is 0.8% to 2%. Accordingly, the amount of carbon source added in the second sintering process is such that the mass content of carbon in the first lithium iron phosphate material is 0.8% to 2%.
[0135] In some embodiments, a step S30 of preparing a second lithium iron phosphate material is further included. S30 includes the following steps: mixing a second lithium source, a second phosphorus source, a second iron source, and a second doping source with a second solvent to obtain a second slurry, drying to remove the second solvent, and performing a third sintering process to obtain a second lithium iron phosphate material. The second doping source includes one or more of titanium, vanadium, niobium, and magnesium.
[0136] In step S30 of preparing the second lithium iron phosphate material, the average particle size of the primary particles of the second lithium iron phosphate material can be adjusted by controlling the third sintering process. Further, the particle size of the second slurry obtained in step S30 can also be adjusted to adjust the average particle size of the primary particles of the second lithium iron phosphate material. It is understandable that the average particle size of the primary particles of the second lithium iron phosphate material can be adjusted by adjusting one or both of the sintering temperature and the slurry particle size.
[0137] Furthermore, in some embodiments, the Dv50 particle size of the second slurry is controlled to be between 50nm and 400nm. As an example, it can be 50nm, 80nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, or within the range consisting of any two of the above point values as end values.
[0138] Furthermore, the second doping source includes one or more of titanium, vanadium, niobium and magnesium. The doping elements in the first doping source and the second doping source may be the same or different.
[0139] Further, the second doping source includes one or more of titanium dioxide, vanadium pentoxide, n-butyl titanate, niobium pentoxide, niobium oxalate, niobium ethoxide, magnesium hydroxide, magnesium nitrate and ammonium metavanadate. The specific types of the first doping source and the second doping source can be the same or different.
[0140] Further, the insulation temperature of the third sintering treatment is 600°C~800°C, and the insulation time is 2h~24h, which can be optionally 2h~6h. As an example, the insulation temperature of the second sintering treatment can be 600°C, 620°C, 640°C, 660°C, 680°C, 700°C, 720°C, 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 800°C, or within the range formed by any two of the above point values as end values. As an example, the insulation time can be 2h, 3h, 4h, 5h, 26h, or within the range formed by any two of the above point values as end values.
[0141] Furthermore, the second lithium iron phosphate material contains a carbon coating layer, and the mass content of carbon in the second lithium iron phosphate material is 0.8% to 2%. Accordingly, a carbon source is also added to the second slurry, and the amount of the carbon source added is based on the mass content of carbon in the second lithium iron phosphate material being 0.8% to 2%.
[0142] As an example, the first lithium source and the second lithium source each independently include, but are not limited to, at least one of lithium hydroxide, lithium oxide, lithium chloride, lithium nitrite, lithium nitrate, lithium oxalate, lithium carbonate, lithium acetate, lithium phosphate, lithium dihydrogen phosphate and lithium hydrogen phosphate.
[0143] As an example, the first phosphorus source and the second phosphorus source each independently include, but are not limited to, at least one of H3PO4, NH4H2PO4, (NH4)2HPO4, LiH2PO4, Li3PO4, and (NH4)3PO4.
[0144] The first iron source and the second iron source are both ferrous iron sources, including but not limited to at least one of ferrous iron oxides and ferrous iron metal salt compounds. As an example, the first iron source and the second iron source each independently include but not limited to at least one of ferrous oxide, ferrous oxalate, ferrous acetate, ferrous chloride and ferrous sulfate.
[0145] As an example, the first solvent and the second solvent each independently include, but are not limited to, one or more of water, ethanol, methanol, N-methylpyrrolidone, acetone, dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and ethylene carbonate (EMC). In a specific example, the first solvent and the second solvent are water.
[0146] The carbon source added in each of the above steps may independently include one or more of glucose, sucrose, citric acid, carboxymethyl cellulose, polyethylene glycol, malic acid, tartaric acid, oxalic acid, salicylic acid, succinic acid, glycine and ethylenediaminetetraacetic acid, but is not limited thereto.
[0147] It is understandable that the drying method in the above-mentioned steps of drying the slurry to remove the solvent includes but is not limited to at least one of spray drying, hot air drying, reduced pressure drying, etc. Optionally, the drying method includes spray drying. Further, the spray drying can be carried out using a high-speed spray dryer; further, the negative pressure of the spray drying is -650 Pa ~ -200 Pa, the inlet temperature is 300℃~360℃, and the outlet temperature is 100℃~140℃.
[0148] The fifth aspect of the present application provides an electrical device, comprising the lithium-ion battery provided by the first aspect of the present application, the positive electrode plate provided by the second aspect of the present application, the positive electrode active material provided by the third aspect of the present application, and at least one of the positive electrode active materials prepared by the preparation method provided by the fourth aspect of the present application.
[0149] The lithium-ion battery and the electrical device of the present application will be described below with reference to the accompanying drawings as appropriate.
[0150] Generally, lithium-ion batteries include a positive electrode sheet, a negative electrode sheet, an electrolyte, and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0151] Positive electrode
[0152] The positive electrode sheet is as described above. Further, in addition to the positive electrode film layer, the positive electrode sheet may also include a positive electrode current collector, wherein the positive electrode current collector is disposed on the positive electrode film layer on at least one surface of the positive electrode current collector.
[0153] As a non-limiting example, the positive electrode current collector has two surfaces opposite to each other in its thickness direction, and the positive electrode film layer is disposed on any one or both of the two opposite surfaces of the positive electrode current collector.
[0154] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. For example, aluminum foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the positive electrode current collector, non-limiting examples of the metal material may include one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the positive electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0155] It is understandable that the battery will be accompanied by lithium (Li) deintercalation and consumption during the charging and discharging process, and the content of Li in the positive electrode active material is different when the battery is discharged to different states. In the enumeration of positive electrode active materials in this application, unless otherwise specified, the content of Li is the initial state of the material. The positive electrode active material is applied to the positive electrode plate in the battery system, and after the charge and discharge cycle, the content of Li in the positive electrode active material contained in the plate usually changes. Among them, the content of Li can be measured by molar content, but is not limited to this. Regarding "the content of Li is the initial state of the material", the initial state of the material refers to the state before the material is added to the positive electrode slurry. It is understandable that the new material obtained by appropriate modification on the basis of the listed positive electrode active materials is also within the scope of positive electrode active materials. The aforementioned appropriate modification refers to the acceptable modification method for the positive electrode active material, and non-limiting examples include coating modification.
[0156] In the list of positive electrode active materials in this application, the content of oxygen (O) is only a theoretical state value. The release of oxygen from the lattice will cause the molar content of oxygen to change, and the actual content of O will fluctuate. Among them, the content of O can be measured by molar content, but is not limited to this.
[0157] In some of the embodiments, the positive electrode film layer may also optionally include a binder. As a non-limiting example, the binder may include one or more of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylate resin.
[0158] In some of the embodiments, in the positive electrode film layer, the mass content of the binder may be 1% to 5%, further 1% to 3%, and optionally 1.6% to 2.0%; as an example, it may be 1%, 1.5%, 1.6%, 2%, 2.5%, 3%, 4%, 5%, or within the range consisting of any two of the above point values as end values.
[0159] In some embodiments, the positive electrode film layer may further include a conductive agent. As a non-limiting example, the conductive agent may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0160] In some of the embodiments, in the positive electrode film layer, the mass content of the conductive agent may be 0.5%~5%, further 1%~3%, and optionally 1.6%~2.0%; as an example, it may be 0.5%, 1%, 1.5%, 1.6%, 2%, 2.5%, 3%, 4%, 5%, or within the range consisting of any two of the above point values as end values.
[0161] In some of the embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components, are dispersed in a solvent to form a positive electrode slurry; the positive electrode slurry is coated on at least one side of the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained. The type of solvent can be selected from but not limited to any one of the aforementioned embodiments, such as N-methylpyrrolidone (NMP). The surface of the positive electrode collector coated with the positive electrode slurry can be on a single surface of the positive electrode collector or on both surfaces of the positive electrode collector. The solid content of the positive electrode slurry can be 40wt%~80wt%. The viscosity of the positive electrode slurry at room temperature can be adjusted to 5000mPa·s~25000mPa·s. When the positive electrode slurry is coated, the coating unit surface density on a dry weight basis (excluding the solvent) can be 320 mg / 1540mm 2 ~600mg / 1540mm 2 ; Optional: 400 mg / 1540mm 2 ~500mg / 1540mm 2 .
[0162] Negative electrode
[0163] The negative electrode plate includes a negative electrode current collector. Further, the negative electrode plate may also include a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material.
[0164] As a non-limiting example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0165] In some of the embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, copper foil may be used as the metal foil. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be obtained by forming a metal material on a polymer material substrate. In the negative electrode current collector, non-limiting examples of the metal material may include one or more of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. In the negative electrode current collector, non-limiting examples of the polymer material substrate may include one or more of substrates such as polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.
[0166] In some of the embodiments, the negative electrode active material may adopt the negative electrode active material for batteries known in the art. As a non-limiting example, the negative electrode active material may include one or more of the following materials: graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. Among them, graphite includes but is not limited to one or more of artificial graphite and natural graphite. Silicon-based materials may include one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. Tin-based materials may include one or more of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0167] Further, the negative electrode active material may include graphite; further, on this basis, the negative electrode active material may also include silicon-based materials, and the mass content of silicon-based materials in the negative electrode active material is 0.5%~20%, as an example, it can be 0.5%, 1%, 2%, 3%, 4%, 5%, 10%, 15%, 20% or any two of the above point values as the end value range, which can be selected as 0.5%~15%, 0.5%~10% or 0.5%~5%. By using graphite and silicon-based materials as negative electrode active materials, the energy density of the battery can be improved, and the rapid lithium insertion performance of the negative electrode plate can be improved.
[0168] In some embodiments, the negative electrode film layer may further include a binder. The binder may include one or more of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0169] In some of the embodiments, in the negative electrode film layer, the mass content of the binder may be 1% to 5%, further 1% to 3%, and optionally 1.6% to 2.0%; as an example, it may be 1%, 1.5%, 1.6%, 2%, 2.5%, 3%, 4%, 5%, or within the range consisting of any two of the above point values as end values.
[0170] In some embodiments, the negative electrode film layer may further include a conductive agent, which may include one or more of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0171] In some of the embodiments, in the negative electrode film layer, the mass content of the conductive agent may be 0.5%~5%, further 1%~3%, and optionally 1.6%~2.0%; as an example, it may be 0.5%, 1%, 1.5%, 1.6%, 2%, 2.5%, 3%, 4%, 5%, or within the range consisting of any two of the above point values as end values.
[0172] In some of the embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0173] In some of the embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (a non-limiting example of the solvent is deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on at least one side of the surface of the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained. The surface of the negative electrode collector coated with the negative electrode slurry can be a single surface of the negative electrode collector or two surfaces of the negative electrode collector. The solid content of the negative electrode slurry can be 40wt%~60wt%. The viscosity of the negative electrode slurry at room temperature can be adjusted to 2000~10000mPa·s. When coating the negative electrode slurry, the coating unit surface density on a dry weight basis (excluding the solvent) can be 110 mg / 1540mm 2 ~300mg / 1540mm 2 .
[0174] Electrolytes
[0175] The electrolyte has the function of conducting ions between the positive electrode and the negative electrode. The present application has no particular restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0176] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0177] In some embodiments, the electrolyte salt may include one or more of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorophosphate (LiPO2F2), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP). Further, the concentration of the electrolyte salt in the electrolyte may be 0.8 mol / L to 2 mol / L, for example, 0.8 mol / L, 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.5 mol / L, 1.6 mol / L, 1.8 mol / L, 2 mol / L, or in a range consisting of any two of the above point values as end values.
[0178] In some embodiments, the solvent is an organic solvent, which may include but is not limited to one or more of acid ester solvents, nitrile solvents, and carbonate solvents. Further, the carboxylate solvent includes one or more of ethyl acetate, methyl acetate, methyl formate, propyl acetate, butyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, propyl butyrate, butyl butyrate, 1,4-butyrolactone, isopropyl acetate, and isoamyl acetate, which may be one or more of ethyl acetate and methyl acetate. Further, the nitrile solvent includes one or more of acetonitrile, monofluoroacetonitrile, difluoroacetonitrile, and trifluoroacetonitrile. Further, the carbonate solvent includes one or more of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), and butylene carbonate.
[0179] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0180] In some embodiments, the additives in the electrolyte may include, but are not limited to, one or more of vinylene carbonate (VC), fluoroethylene carbonate (FEC), difluoroethylene sulfate (DTD), difluoroethylene carbonate (DFEC), trifluoromethylethylene carbonate (TFPC), and the like.
[0181] Further, the additives in the electrolyte include vinylene carbonate (VC), fluoroethylene carbonate (FEC) and diethylene sulfate (DTD).
[0182] Furthermore, the mass content of vinylene carbonate (VC) in the electrolyte may be 0.5% to 5%. As an example, it may be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%, or within a range consisting of any two of the above point values as end values.
[0183] Furthermore, the mass content of fluoroethylene carbonate (FEC) in the electrolyte may be 0.5% to 5%. For example, it may be 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 4%, 5%, or within a range consisting of any two of the above point values as end values.
[0184] Further, the mass content of vinyl sulfate (DTD) in the electrolyte can be 0.2% to 2%, as an example, it can be 0.2%, 0.5%, 1%, 1.5%, or within the range formed by any two of the above point values as end values. Further, the electrolyte can optionally use an electrolyte with a higher conductivity, for example, the conductivity of the electrolyte is 12mS / cm to 20mS / cm, as an example, it can be 12mS / cm, 13mS / cm, 14mS / cm, 15mS / cm, 16mS / cm, 17mS / cm, 18mS / cm, 19mS / cm, 20mS / cm, or within the range formed by any two of the above point values as end values.
[0185] Isolation film
[0186] In some embodiments, the secondary battery further includes a separator.
[0187] Generally, a secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is set between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.
[0188] The present application has no particular limitation on the type of isolation membrane, and any known porous isolation membrane with good chemical stability and mechanical stability may be selected.
[0189] In some embodiments, the material of the isolation membrane may include one or more of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0190] In some embodiments, the isolation film has a thickness of 6 μm to 40 μm, and may be 12 μm to 20 μm.
[0191] A lithium-ion battery includes at least one battery cell. A lithium-ion battery may include one or more battery cells.
[0192] In this application, unless otherwise specified, "battery cell" refers to a basic unit that can realize the mutual conversion of chemical energy and electrical energy, and further, generally speaking, at least includes a positive electrode sheet, a negative electrode sheet and an electrolyte. During the battery charging and discharging process, active ions are embedded and released back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting active ions between the positive electrode sheet and the negative electrode sheet.
[0193] The present application has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The lithium-ion battery shown is a battery cell, which is an example of a battery cell with an exemplary square structure.
[0194] In some embodiments, the lithium-ion battery may include an outer package. The outer package may be used to encapsulate the electrode assembly and the electrolyte. In some embodiments, the outer package of the lithium-ion battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer package of the lithium-ion battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and further, non-limiting examples of plastic may include one or more of polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0195] In some of these embodiments, reference Figure 2 , the outer packaging may include a shell 51 and a cover plate 53. Among them, the shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 can be covered on the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation membrane can form an electrode assembly 52 through a winding process or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, and those skilled in the art can select according to actual needs.
[0196] In some embodiments, the lithium-ion battery may be a battery module or a battery pack. The battery module includes at least one battery cell. The number of battery cells contained in the battery module may be one or more, and those skilled in the art may select a suitable number according to the application and capacity of the battery module.
[0197] Figure 3 4 is an example of a battery module. Figure 3 In the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0198] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0199] In some of the embodiments, the battery modules may be assembled into a battery pack. The battery pack may contain one or more battery modules. Those skilled in the art may select a suitable number according to the application and capacity of the battery pack.
[0200] Figure 4 and Figure 5 1 is a battery pack 1 as an example. Figure 4 and Figure 5 The battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3. The upper box body 2 can cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 can be arranged in the battery box in any manner.
[0201] In addition, one embodiment of the present application further provides an electrical device, which includes the above-mentioned lithium-ion battery provided in the present application. The lithium-ion battery can be used as a power source for the electrical device, and can also be used as an energy storage unit for the electrical device. The electrical device may include mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc., but are not limited thereto. Among them, the mobile device may be, for example, a mobile phone, a laptop computer, etc.; the electric vehicle may be, for example, a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc., but are not limited thereto.
[0202] As an electrical device, a lithium-ion battery can be selected according to its usage requirements.
[0203] Figure 6The power consumption device 6 is taken as an example. The power consumption device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the power consumption device's requirements for high power and high energy density of lithium-ion batteries, a battery pack or a battery module can be used.
[0204] Another example of a device may be a mobile phone, a tablet computer, a notebook computer, etc. Such a device is usually required to be thin and light, and a lithium-ion battery may be used as a power source.
[0205] In order to make the technical problems, technical solutions and beneficial effects solved by the present application clearer, the present application will be further described in detail below in conjunction with the embodiments and drawings. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present application and its applications. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0206] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0207] Example 1
[0208] (1) Preparation of positive electrode
[0209] 1. Preparation of the first lithium iron phosphate particles (high titanium doping):
[0210] Weigh lithium carbonate, ferric oxide, phosphoric acid, titanium dioxide (based on the total weight of lithium iron phosphate particles, the amount of titanium dioxide added meets the titanium content in the prepared first lithium iron phosphate particles, as shown in Table 1) and carbon source (polyethylene glycol, the amount of polyethylene glycol added meets the first sintering after the subsequent completion of the carbon content of the first sintering product of 0.15% of the weight, as shown in Table 1). Mix the above substances and add water to obtain the first slurry. After the first slurry is mixed evenly with a ball mill, it is then ground with a sand mill to control its Dv50 to 680nm. The ground first slurry is spray dried. The dried material is loaded into a sintering furnace for the first sintering treatment, the heating rate is controlled to 5℃ / min, the insulation temperature is controlled to 750℃, and the insulation time is 4h. After cooling with the furnace, the material is taken and crushed by a mechanical mill to obtain a powder.
[0211] The powder obtained in the above steps, the carbon source (based on the total weight of the first lithium iron phosphate particles, the amount of carbon source added to meet the carbon content of the product after the second sintering is 1.2%) and water are processed by ball milling and sand milling to obtain a slurry. The obtained slurry is then spray dried. The dried material is loaded into a sintering furnace for the second sintering, the heating rate is controlled at 5°C / min, the sintering temperature is 750°C, and the sintering time is 4h. After that, it is cooled with the furnace. After the material is cooled, it is crushed and demagnetized to obtain the first lithium iron phosphate particles.
[0212] 2. Preparation of the second lithium iron phosphate particles (low titanium doping):
[0213] Weigh lithium carbonate, ferric oxide, phosphoric acid, titanium dioxide (based on the total weight of lithium iron phosphate particles, the amount of titanium dioxide added meets the titanium content in the prepared lithium iron phosphate particles, as shown in Table 1) and carbon source (the amount of carbon source added meets the carbon content of 1.2% of the weight of the sintered product after subsequent sintering). Add water to the above substances to obtain a second slurry. After the second slurry is mixed evenly with a ball mill, it is then ground with a sand mill to control the slurry Dv50 to 180nm. The ground slurry is spray dried. The dried reactants are loaded into a sintering furnace for sintering (i.e., the third sintering treatment), the heating rate is controlled to 5°C / min, the insulation temperature is controlled to 780°C, and the insulation time is 4h. After the material is cooled, the second lithium iron phosphate particle finished product can be obtained by air flow crushing.
[0214] 3. The detection method for the first lithium iron phosphate particles prepared in step 1 and the second lithium iron phosphate particles prepared in step 2 is as follows:
[0215] 3.1 The method for detecting the carbon mass content in the first sintered product obtained in step 1, the first lithium iron phosphate particles, and the second lithium iron phosphate obtained in step 2 is as follows: refer to GB / T 33822-2017.
[0216] 3.2 The BET specific surface area detection method of the first lithium iron phosphate particles prepared in step 1 and the second lithium iron phosphate material prepared in step 2 is as follows: Referring to GB / T19587-2017, the nitrogen adsorption specific surface area analysis test method is used for testing, and the BET (Brunauer Emmett Teller) method is used for calculation, wherein the nitrogen adsorption specific surface area analysis test can be performed by the Tri-Star3020 specific surface area pore size analysis tester of Micromeritics, USA. The BET specific surface areas of the first lithium iron phosphate particles and the second lithium iron phosphate material are 6m 2 / g and 15m 2 / g.
[0217] 3.3 The method for detecting the titanium content in the first lithium iron phosphate particles or the second lithium iron phosphate obtained is as follows: ICP test is adopted with reference to GB / T 33822-2017. The specific operation method is: weigh a certain weight of the first lithium iron phosphate particles, then digest them with concentrated nitric acid, then dilute the solution, and test the weight of titanium metal in the diluted solution by ICP, and calculate the titanium content in the first lithium iron phosphate particles according to the tested weight of titanium metal and the weight of the first lithium iron phosphate particles.
[0218] 4. Preparation of positive electrode
[0219] The first lithium iron phosphate and the second lithium iron phosphate are used as positive electrode active materials, and the first lithium iron phosphate, the second lithium iron phosphate, the conductive agent carbon black (Super P), and the binder polyvinylidene fluoride (PVDF) are uniformly mixed in an appropriate amount of solvent N-methylpyrrolidone (NMP) at a mass ratio of 48:48:2.7:1.3 to obtain a positive electrode slurry.
[0220] The positive electrode slurry is coated on the positive electrode current collector aluminum foil and dried to form a positive electrode film layer; the positive electrode sheet is obtained through the processes of drying, cold pressing, slitting, cutting and the like.
[0221] (2) Preparation of negative electrode sheet:
[0222] The negative electrode active material artificial graphite, conductive agent conductive carbon black (Super P), binder styrene butadiene rubber (SBR) and thickener sodium carboxymethyl cellulose (CMC) are mixed evenly according to a weight percentage of 95:1.0:2.0:2.0 and deionized water is added. After stirring and dispersion, the negative electrode slurry is obtained. The negative electrode slurry is coated on the substrate Cu foil, and after drying and cold pressing, a negative electrode film layer is formed, and then the negative electrode sheet is obtained after slitting and sheeting. The single-sided thickness of the negative electrode film layer is 54μm; when the negative electrode slurry is coated, the coating unit surface density based on dry weight (excluding solvent) can be 200mg / 1540mm 2 .
[0223] (3) Isolation film
[0224] A 12μm thick polypropylene isolation film was selected.
[0225] (4) Preparation of electrolyte
[0226] Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and ethyl methyl carbonate (DMC) were mixed at a mass ratio of 30:30:40 to obtain an organic solvent.
[0227] Vinyl carbonate (VC), fluoroethylene carbonate (FEC), vinyl sulfate (DTD) and fully dried LiPF6 are dissolved in the above organic solvent to prepare an electrolyte with a LiPF6 concentration of 1 mol / L. In the total mass of the electrolyte, the mass content of vinyl carbonate (VC) is 2.5wt%, the mass content of fluoroethylene carbonate (FEC) is 1wt%, and the mass content of vinyl sulfate (DTD) is 0.5wt%.
[0228] (5) Preparation of batteries:
[0229] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order and wound to obtain an electrode assembly; the electrode assembly is placed in an outer package, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, exhausting and other processes, a lithium-ion battery is finally obtained. The electrolyte injection coefficient is 2.4 g / Ah.
[0230] Embodiment 2-3
[0231] It is basically the same as Example 1, except that in the preparation step (1) of the positive electrode plate, the average particle size of the primary particles of the first lithium iron phosphate prepared in step 1 is adjusted by regulating the Dv50 particle size after grinding the first slurry. The specific parameters are shown in Table 1.
[0232] Embodiment 4-5
[0233] It is basically the same as Example 1, except that in the preparation step (1) of the positive electrode plate, the doping amount of titanium element in the first lithium iron phosphate prepared in step 1 is achieved by adjusting the amount of titanium dioxide added and appropriately adjusting the sintering process (in Example 5, a larger doping amount is obtained by reducing the mass content of carbon in the first sintered product of the first lithium iron phosphate). The specific parameters are shown in Table 1.
[0234] Embodiment 6-7
[0235] It is basically the same as Example 1, except that in the preparation step (1) of the positive electrode plate, the average particle size of the primary particles of the second lithium iron phosphate prepared in step 2 is achieved by adjusting the Dv50 particle size after grinding the second slurry. The specific parameters are shown in Table 1.
[0236] Embodiment 8-9
[0237] It is basically the same as Example 1, except that in the preparation step (1) of the positive electrode plate, the doping amount of the titanium element in the second lithium iron phosphate prepared in step 2 is achieved by adjusting the amount of titanium dioxide added and appropriately adjusting the sintering process (for example, in Example 9, the Dv50 particle size of the second slurry after grinding is regulated to be 290nm. This is because the increase in the doping of a higher content of titanium metal elements will inhibit grain growth, so the Dv50 particle size is increased to obtain particles with the same average particle size). The specific parameters are shown in Table 1.
[0238] Embodiment 10-11
[0239] It is basically the same as Example 1, except that in the preparation step (1) of the positive electrode sheet, the mass ratio of the first lithium iron phosphate and the second lithium iron phosphate in step 4 is different. Specifically, the mass content of the first lithium iron phosphate in the total amount of the first lithium iron phosphate and the second lithium iron phosphate is as shown in Table 1.
[0240] Embodiment 12-13
[0241] It is basically the same as Example 1, and the parameters of the differences are shown in Table 1; the type of doping element is changed by changing the type of dopant added, and the amount of dopant added is adjusted according to its doping amount; Example 12 and Example 13 respectively use vanadium pentoxide and niobium pentoxide to replace the titanium dioxide in Example 1.
[0242] Comparative Example 1
[0243] Comparative Example 1 is substantially the same as Example 8, except that in the step (1) of preparing the positive electrode sheet, the doping amount of the titanium element in the first lithium iron phosphate prepared in step 1 is as shown in Table 1.
[0244] The following is a performance test.
[0245] (1) The average particle size of the primary particles of the first lithium iron phosphate particles or the second lithium iron phosphate particles and the average mass content of the doping elements can be tested by the following method:
[0246] 1.1 Disassemble the battery to obtain the positive electrode sheet, peel off the positive electrode film layer of the positive electrode sheet, use acetone to fully wash the positive electrode film layer, filter and dry to obtain powder. Take 0.05g of the evenly mixed powder and dissolve it in 40mL of anhydrous ethanol, then add an appropriate amount of dispersant, stir evenly to obtain a suspension, take 2mL of the suspension and 2mL of anhydrous ethanol and mix them, then perform ultrasonic treatment, the ultrasonic power is 480W, the ultrasonic time is 5min, and the uniformly dispersed suspension is obtained. Take an appropriate amount of the middle layer suspension for transmission electron microscopy test to obtain a transmission electron microscope image.
[0247] 1.2 Select 5-10 transmission electron microscope images with 50 to 100 particles as the sampling area, and ensure that at least 500 particles are tested. Then, the projection area of each primary particle in each sampling area can be counted through the Avizo 3D software image processing software, which is the primary particle cross-sectional area S. Among them, when identifying primary particles, for particles with obvious adhesion, manual identification and software identification can be combined to determine whether the particles belong to primary particles or secondary particles. The equivalent circle method is used to obtain the equivalent circle diameter of the primary particle, which is the primary particle size d of the primary particle; at the same time, the transmission electron microscope accessory EDS energy spectrum is used to perform elemental analysis on each primary particle. The test point is the middle part of the transmission surface of each particle, and the mass content of the doping element of each primary particle in the three sampling areas is obtained.
[0248] 1.3 The mass content of the doping element and the corresponding primary particle size of each primary particle in multiple sampling areas are counted, for example, with the primary particle size as the horizontal coordinate and the mass content of the doping element as the vertical coordinate, and the position of each primary particle in the coordinate is shown. Through the distribution of the primary particles in the coordinate, it can be clearly obtained that there are two areas where the mass content of the doping element is relatively concentrated. For the primary particles with a small particle size but a high doping amount and the primary particles with a large particle size but a small doping amount in the statistical process, they are divided into the first lithium iron phosphate particles and the second lithium iron phosphate particles based on the doping amount, which are located on the upper and lower sides parallel to the horizontal coordinate, respectively, wherein the area with a higher mass content of the doping element is the first lithium iron phosphate material, and the area with a lower mass content of the doping element is the second lithium iron phosphate material. It is worth noting that in the same positive electrode plate, there is a large difference in the doping amount of the first lithium iron phosphate material and the second lithium iron phosphate material. In the present application, the difference between the average mass content of the doping element in the first lithium iron phosphate material and the average mass content of the doping element in the second lithium iron phosphate material is controlled to be 1000ppm~8500ppm. Therefore, in the reverse detection of the first lithium iron phosphate material and the second lithium iron phosphate material in the positive electrode plate, it can be obviously obtained that the area with a higher mass content of the doping element is the first lithium iron phosphate material, and the area with a lower mass content of the doping element is the second lithium iron phosphate material.
[0249] 1.4 Count the sum of the primary particle sizes of all first lithium iron phosphate materials and divide it by the total number of all first lithium iron phosphate materials to obtain the average primary particle size of the first lithium iron phosphate materials. Count the sum of the mass contents of the doping elements in all first lithium iron phosphate materials and divide it by the total number of all first lithium iron phosphate materials to obtain the average mass content of the doping elements in the first lithium iron phosphate materials; as shown in Table 1.
[0250] 1.5 Count the sum of the primary particle sizes of all second lithium iron phosphate materials and divide it by the total number of all second lithium iron phosphate materials to obtain the average primary particle size of the second lithium iron phosphate materials. Count the sum of the mass contents of the doping elements in all second lithium iron phosphate materials and divide it by the total number of all second lithium iron phosphate materials to obtain the average mass content of the doping elements in the second lithium iron phosphate materials; as shown in Table 1.
[0251] (2) Pole compaction density test method:
[0252] When the pole piece is coated on one side, the compaction density of the film layer on one side of the pole piece = m / (V1-V2); when the pole piece is coated on both sides, the compaction density of the film layer on one side of the pole piece = m / [2×(V1-V2)], where m represents the weight of the film layer, V1 represents the volume of the pole piece, and V2 represents the volume of the current collector. m can be obtained by subtracting the weight of the current collector from the weight of the pole piece. The product of the surface area of the pole piece and the thickness of the pole piece is the volume V1 of the pole piece, and the product of the surface area of the pole piece and the thickness of the current collector is V2. The thickness of the current collector and the thickness of the pole piece are obtained by measuring the thickness of the empty foil in the pole lug area and the thickness of the film area with a micrometer.
[0253] (3) DCR (25°C, 10% SOC) test
[0254] Capacity calibration: After the lithium ion batteries prepared in the embodiments and comparative examples were kept at 25°C for 2 hours, they were charged to 3.65V at a constant current of 0.33C, and then charged to 0.05C at a constant voltage of 3.65V. After the charging was completed, the tested batteries were kept at 25°C for 2 hours, and then discharged to 2.5V at a direct current of 0.33C, and the discharge capacity at room temperature was recorded as C0;
[0255] Adjust SOC (battery state of charge): After keeping the calibrated lithium-ion battery at 25°C for 2 hours, discharge it at a 1 / 3C0 discharge rate for 144 minutes to adjust the lithium-ion battery capacity to 10% SOC;
[0256] Power test: After the lithium-ion battery with 10% SOC is left to stand at 25℃ for 2h, it is discharged at a discharge rate of 3C0 for 30s under a pulse current I. The voltage before 3C0 discharge is recorded as V1, and the voltage at the end of 30s discharge is recorded as V2. The value of the DC internal resistance DCR = (V1-V2) / I is calculated. This data can be used to characterize the power performance of the battery.
[0257] (4) Test method for volume energy density.
[0258] Capacity test of battery cells: let the battery cells stand at 25℃ for 2h to ensure that the temperature of the battery cells is 25℃, then discharge the battery at a constant current of 1 / 3C to 2.0V; after standing for 5min, charge the battery cells at a constant current of 1 / 3C to 3.65V, continue to charge at a constant voltage of 3.65V until the current is 0.05C, let stand for 5min, discharge the battery cells at a constant current of 1 / 3 to 2.0V, record the total discharge capacity C0 released by the battery cells, the total discharge energy is E0, and the unit of total discharge energy is Wh.
[0259] Battery cell volume measurement: Use a caliper to measure the length, width, and height of the battery's outer surface, and calculate the volume V0 of the single cell, in L.
[0260] Calculation of volume energy density: Battery cell discharge energy E0 / battery volume V0 is the volume energy density of the battery cell, in units of Wh / L.
[0261] Some parameters and performance test results of each embodiment and comparative example are shown in Table 1 and Table 2, respectively.
[0262] Table 1
[0263]
[0264] In Table 1, the first LFP and the second LFP are the first lithium iron phosphate material and the second lithium iron phosphate material, respectively. The mass content of the first LFP refers to the mass content of the first lithium iron phosphate material in the total amount of the first lithium iron phosphate material and the second lithium iron phosphate material. The carbon content refers to the mass content of carbon in the product obtained by the first sintering. The doping amount difference refers to the difference between the average mass content of the doping element in the first lithium iron phosphate material and the average mass content of the doping element in the second lithium iron phosphate material.
[0265] Table 2
[0266]
[0267] The first LFP used in Comparative Example 1 has a low mass content of titanium metal elements doped in it, so the first LFP has a large kinetic performance, which makes the internal resistance DCR of its battery large, indicating that its power performance is poor and its volume energy density is also low. Each embodiment uses a first LFP with a large doping amount and an average primary particle size and a second LFP with a small average primary particle size as a positive electrode active material, and the prepared battery has both a high volume energy density and a low internal resistance DCR, indicating that it has both good energy density and power performance.
[0268] The difference between Examples 1 to 3 is that the average particle size of the primary particles of the first lithium iron phosphate material in the positive electrode plate is achieved by adjusting the Dv50 particle size of the first slurry after grinding in the preparation process. By controlling the average particle size range of the primary particles of the first lithium iron phosphate material and grading it with the second lithium iron phosphate material, a good tight stacking effect can be obtained, which is beneficial to improving the compaction density of the positive electrode plate. As the average particle size of the primary particles of the first lithium iron phosphate material increases, the kinetic properties of the first lithium iron phosphate material deteriorate, so the DCR value of the battery increases, indicating that the power performance has decreased. In addition, since the kinetic properties of the first lithium iron phosphate material deteriorate, the charge and discharge capacity of the battery is affected, so the volume energy density of the battery first increases and then decreases.
[0269] The difference between Examples 1 and 4-5 is the doping amount of titanium in the first lithium iron phosphate in the positive electrode plate, which is achieved by adjusting the amount of titanium dioxide added and the sintering process appropriately in the preparation process. For example, in Example 5, a larger doping amount is obtained by reducing the mass content of carbon in the first sintered product of the first lithium iron phosphate. As the doping amount of titanium in the first lithium iron phosphate increases, the DCR value of the battery decreases, indicating that the power performance of the battery is improved; and as the doping amount of titanium in the first lithium iron phosphate increases, it will affect the capacity of the positive electrode active material, so the volume energy density of the battery first increases and then decreases.
[0270] The difference between Examples 1 and 6-7 is that the average particle size of the primary particles of the second lithium iron phosphate prepared in the positive electrode sheet is achieved by regulating the Dv50 particle size after grinding the second slurry in the preparation process. As the average particle size of the primary particles of the second lithium iron phosphate material increases, the difference in the average particle size of the primary particles between the two lithium iron phosphate materials gradually decreases. By controlling the difference in the average particle size of the primary particles between the two lithium iron phosphate materials within a suitable range, the grading of the two can obtain a higher tight stacking effect, so that the compaction density of the positive electrode sheet can obtain a higher compaction density. As the average particle size of the primary particles of the second lithium iron phosphate material increases, the kinetic properties of the second lithium iron phosphate material deteriorate, so the DCR value of the battery increases slightly, indicating that the power performance decreases slightly. In addition, due to the deterioration of the kinetic properties of the second lithium iron phosphate material, the charge and discharge capacity of the battery is affected, so the volume energy density of the battery first increases and then decreases.
[0271] The difference between Example 1 and Examples 8-9 is that the doping amount of titanium in the second lithium iron phosphate prepared in the positive electrode plate is achieved by adjusting the amount of titanium dioxide added and appropriately adjusting the sintering process. For example, in Example 9, the Dv50 particle size of the second slurry after grinding is regulated to be 290nm. This is because the increase in the doping of a higher content of titanium metal elements will inhibit grain growth, so the Dv50 particle size is increased to obtain particles with the same average particle size. As the doping amount of titanium in the second lithium iron phosphate increases, the DCR value of the battery decreases, indicating that the power performance of the battery is improved; and as the doping amount of titanium in the second lithium iron phosphate increases, it will affect the capacity of the positive electrode active material, so the volume energy density of the battery increases first and then decreases.
[0272] The difference between Example 1 and Examples 10-11 is that the mass ratio of the first lithium iron phosphate and the second lithium iron phosphate in the positive electrode plate is different. As the mass content of the first lithium iron phosphate in the total amount of the first lithium iron phosphate and the second lithium iron phosphate increases, the compaction density of the positive electrode plate first increases and then decreases. When the mass content of the first lithium iron phosphate is in the range of 30%-70%, the first lithium iron phosphate and the second lithium iron phosphate have a better compaction effect, so a better compaction density can be obtained, so that the volume energy density of the battery first increases and then decreases. As the amount of the first lithium iron phosphate with a large particle size increases, the DCR value of the battery increases accordingly. In this way, further controlling the mass content of the first lithium iron phosphate in the range of 30%-70% can enable the battery to have both better power performance and volume energy density.
[0273] The difference between Examples 1 and 12-13 is that the doping elements in the first lithium iron phosphate and the second lithium iron phosphate are different. In the preparation process, the type of doping element is changed by changing the type of dopant added, and the amount of dopant added is adjusted according to its doping amount; Example 12 and Example 13 use vanadium pentoxide and niobium pentoxide to replace titanium dioxide in Example 1. It can be seen that the first and second lithium iron phosphates doped with vanadium and niobium and the first and second lithium iron phosphates doped with titanium can make the battery have good energy density and power performance compared with Comparative Example 1.
[0274] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0275] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.
Claims
1. A lithium ion battery, characterized in that: It includes a positive electrode plate, the positive electrode plate includes a positive electrode film layer, the positive electrode film layer includes a positive electrode active material, the positive electrode active material includes a first lithium iron phosphate material and a second lithium iron phosphate material mixed with each other, the first lithium iron phosphate material and the second lithium iron phosphate material contain doping elements, the doping elements in the first lithium iron phosphate material and the second lithium iron phosphate material each independently include one or more of titanium, vanadium, niobium and magnesium, the difference between the average mass content of the doping elements in the primary particles of the first lithium iron phosphate material and the average mass content of the doping elements in the primary particles of the second lithium iron phosphate material is 1000ppm~8500ppm, the average particle size of the primary particles of the first lithium iron phosphate material is greater than the average particle size of the primary particles of the second lithium iron phosphate material, the average mass content of the doping elements in the primary particles of the first lithium iron phosphate material is 3000ppm~10000ppm, and the average mass content of the doping elements in the primary particles of the second lithium iron phosphate material is 500ppm~5000ppm.
2. The lithium-ion battery according to claim 1, characterized in that The lithium-ion battery meets one or more of the following characteristics: (1) The average particle size of the primary particles of the first lithium iron phosphate material is 500 nm to 3100 nm; (2) The average primary particle size of the second lithium iron phosphate material is 120 nm to 600 nm.
3. The lithium ion battery according to claim 1, characterized in that The lithium-ion battery meets one or more of the following characteristics: (1) The average particle size of the primary particles of the first lithium iron phosphate material is 650nm~2600nm; (2) The average primary particle size of the second lithium iron phosphate material is 150 nm to 580 nm.
4. The lithium ion battery according to claim 1, characterized in that The difference between the average primary particle size of the first lithium iron phosphate material and the average primary particle size of the second lithium iron phosphate material is 200 nm to 2800 nm.
5. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The average mass content of the doping element in the primary particles of the first lithium iron phosphate material is 4500ppm-10000ppm.
6. The lithium ion battery according to claim 5, characterized in that The average mass content of the doping element in the primary particles of the first lithium iron phosphate material is 4500ppm-9000ppm.
7. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The average mass content of the doping element in the primary particles of the second lithium iron phosphate material is 1000ppm-5000ppm.
8. The lithium ion battery according to claim 7, characterized in that The average mass content of the doping element in the primary particles of the second lithium iron phosphate material is 1000ppm-4000ppm.
9. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The lithium-ion battery meets one or more of the following characteristics: (1) The BET specific surface area of the first lithium iron phosphate material is 3 m 2 / g~9m 2 / g; (2) The BET specific surface area of the second lithium iron phosphate material is 10 m 2 / g~25m 2 / g.
10. The lithium ion battery according to any one of claims 1 to 4, characterized in that: Based on the total mass of the first lithium iron phosphate material and the second lithium iron phosphate material, the mass content of the first lithium iron phosphate material is 10% to 90%.
11. The lithium ion battery according to claim 10, characterized in that Based on the total mass of the first lithium iron phosphate material and the second lithium iron phosphate material, the mass content of the first lithium iron phosphate material is 30% to 70%.
12. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The first lithium iron phosphate material and the second lithium iron phosphate material both contain a carbon coating layer, and the mass content of carbon in the positive electrode active material is 0.8% to 2%.
13. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The positive electrode active material accounts for 80% to 98% by mass in the positive electrode film layer.
14. The lithium ion battery according to any one of claims 1 to 4, characterized in that: One or more of the following conditions are met: (1) The compaction density of the positive electrode film layer on one side of the positive electrode sheet is 2.3 g / cc to 2.8 g / cc; (2) The DC internal resistance of the lithium-ion battery at 25° C. and 10% SOC is 800 mΩ to 1300 mΩ.
15. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The lithium-ion battery also includes a negative electrode plate, which includes a negative electrode film layer, which includes a negative electrode active material, and the negative electrode active material includes one or more of graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate.
16. The lithium ion battery according to claim 15, characterized in that The negative electrode active material includes graphite.
17. The lithium ion battery according to claim 15, characterized in that The negative electrode active material includes graphite and silicon-based material. In the negative electrode active material, the mass content of the silicon-based material is 0.5% to 20%.
18. The lithium ion battery according to any one of claims 1 to 4, characterized in that: The lithium-ion battery also includes an electrolyte, and the conductivity of the electrolyte is 12mS / cm-20mS / cm.
19. A positive electrode plate, characterized in that: The positive electrode plate includes a positive electrode film layer, the positive electrode film layer includes a positive electrode active material, the positive electrode active material includes a first lithium iron phosphate material and a second lithium iron phosphate material mixed with each other, the first lithium iron phosphate material and the second lithium iron phosphate material contain doping elements, the doping elements in the first lithium iron phosphate material and the second lithium iron phosphate material each independently include one or more of titanium, vanadium, niobium and magnesium, the difference between the average mass content of the doping elements in the first lithium iron phosphate material and the average mass content of the doping elements in the second lithium iron phosphate material is 1000ppm~8500ppm, the average particle size of the primary particles of the first lithium iron phosphate material is greater than the average particle size of the primary particles of the second lithium iron phosphate material, the average mass content of the doping elements in the first lithium iron phosphate material is 3000ppm~10000ppm, and the average mass content of the doping elements in the second lithium iron phosphate material is 500ppm~5000ppm.
20. A positive electrode active material, characterized in that: The positive electrode active material includes a first lithium iron phosphate material and a second lithium iron phosphate material, the first lithium iron phosphate material and the second lithium iron phosphate material contain doping elements, the doping elements in the first lithium iron phosphate material and the second lithium iron phosphate material each independently include one or more of titanium, vanadium, niobium and magnesium, the difference between the average mass content of the doping elements in the first lithium iron phosphate material and the average mass content of the doping elements in the second lithium iron phosphate material is 1000ppm~8500ppm, the average particle size of the primary particles of the first lithium iron phosphate material is greater than the average particle size of the primary particles of the second lithium iron phosphate material, the average mass content of the doping elements in the first lithium iron phosphate material is 3000ppm~10000ppm, and the average mass content of the doping elements in the second lithium iron phosphate material is 500ppm~5000ppm.
21. A method for preparing a positive electrode active material, characterized in that: The steps include: Prepare a first lithium iron phosphate material and a second lithium iron phosphate material, wherein the first lithium iron phosphate material and the second lithium iron phosphate material contain doping elements, and the doping elements in the first lithium iron phosphate material and the second lithium iron phosphate material independently include one or more of titanium, vanadium, niobium and magnesium; Mixing the first lithium iron phosphate material and the second lithium iron phosphate material to obtain the positive electrode active material; Among them, the difference between the average mass content of the doping element in the first lithium iron phosphate material and the average mass content of the doping element in the second lithium iron phosphate material is 1000ppm~8500ppm, the average particle size of the primary particles of the first lithium iron phosphate material is larger than the average particle size of the primary particles of the second lithium iron phosphate material, the average mass content of the doping element in the first lithium iron phosphate material is 3000ppm~10000ppm, and the average mass content of the doping element in the second lithium iron phosphate material is 500ppm~5000ppm.
22. The preparation method according to claim 21, characterized in that: At least one of the following conditions is met: (1) Preparing the first lithium iron phosphate material comprises the following steps: mixing a first lithium source, a first phosphorus source, a first iron source and a first doping source with a first solvent to obtain a first slurry, drying to remove the first solvent, and performing a first sintering treatment; performing a second sintering treatment on the powder obtained by the first sintering treatment, wherein the insulation temperature of the second sintering treatment is higher than the insulation temperature of the first sintering treatment, to obtain the first lithium iron phosphate material; the first doping source comprises one or more of titanium, vanadium, niobium and magnesium; (2) The preparation of the second lithium iron phosphate material comprises the following steps: mixing a second lithium source, a second phosphorus source, a second iron source and a second doping source with a second solvent to obtain a second slurry, drying to remove the second solvent, and performing a third sintering treatment to obtain a second lithium iron phosphate material; the second doping source comprises one or more of titanium, vanadium, niobium and magnesium.
23. The preparation method according to claim 22, characterized in that: The first doping source and the second doping source independently include one or more of titanium dioxide, vanadium pentoxide, n-butyl titanate, niobium pentoxide, niobium oxalate, niobium ethoxide, magnesium hydroxide, magnesium nitrate and ammonium metavanadate.
24. The preparation method according to any one of claims 22 to 23, characterized in that: The preparation method meets one or more of the following conditions: (1) The first sintering treatment has a holding temperature of 500°C to 760°C and a holding time of 1h to 6h; (2) The holding temperature of the second sintering treatment is 720°C to 780°C, and the holding time is 2h to 12h; (3) The insulation temperature of the third sintering treatment is 600°C to 800°C, and the insulation time is 2h to 24h.
25. The preparation method according to any one of claims 22 to 23, characterized in that: The preparation method meets one or more of the following conditions: (1) further comprising the step of controlling the Dv50 particle size of the first slurry to be between 350 nm and 1200 nm; (2) The method further includes controlling the Dv50 particle size of the second slurry to be between 50 nm and 400 nm.
26. The preparation method according to any one of claims 22 to 23, characterized in that: The first lithium iron phosphate material and the second lithium iron phosphate material both contain a carbon coating layer, and the mass content of carbon in the first lithium iron phosphate material or in the second lithium iron phosphate material is independently 0.8% to 2%; The mass content of carbon element in the powder obtained by the first sintering process is 0.01%~0.79%.
27. An electrical device, characterized in that: The invention comprises at least one of the lithium ion battery according to any one of claims 1 to 18, the positive electrode sheet according to claim 19, the positive electrode active material according to claim 20, and the positive electrode active material prepared by the preparation method according to any one of claims 21 to 26.
Citation Information
Patent Citations
High-energy-density lithium iron phosphate battery
CN111403732A
Lithium iron phosphate positive electrode active material, preparation method thereof, positive electrode plate and battery
CN114068919A
Lithium iron phosphate positive pole piece and related secondary battery, battery module, battery pack and electric device
CN117413385A
Positive electrode active material, positive electrode sheet, secondary battery, battery module, battery pack, and electric device
CN117461158A
Lithium iron phosphate material as well as preparation method and application thereof
CN117810423A
Cited By
Positive electrode material as well as preparation method and application thereof
CN120955127A